Anti-inflammatory activity of horseradish (Armoracia rusticana) root extracts in LPS-stimulated macrophages. Issue 12 (28th September 2015) - Marzocco, Stefania; Calabrone, Luana; Adesso, Simona; Larocca, Marilena; Franceschelli, Silvia; Autore, Giuseppina; Martelli, Giuseppe; Rossano, Rocco
Abstract : Horseradish ( Armoracia rusticana ) is a perennial crop belonging to the Brassicaceae family. Abstract : Horseradish ( Armoracia rusticana ) is a perennial crop belonging to the Brassicaceae family. Horseradish root is used as a condiment due to its extremely pungent flavour, deriving from the high content of glucosinolates and their breakdown products such as isothiocyanates and other sulfur compounds. Horseradish also has a long history in ethnomedicine. In this study the anti-inflammatory potential of three accessions of Armoracia rusticana on lipopolysaccharide from E. coli treated J774A.1 murine macrophages was evaluated. Our results demonstrate that Armoracia rusticana reduced nitric oxide, tumor necrosis factor-α and interleukin-6 release and nitric oxide synthase and cyclooxygenase-2 expression in macrophages, acting on nuclear transcription factor NF-κB p65 activation. Moreover Armoracia rusticana reduced reactive oxygen species release and increased heme-oxygenase-1 expression, thus contributing to the cytoprotective cellular effect during inflammation.